Development of screening method for tetracycline residues in pork (Sus scrofa domesticus) - Toralba, Joanna V.; Dusaban, Lance Frederick C.; Abana, Karla Keith S.; Kwok, Jellian Razzele A. (2020)
Antimicrobial residues in pork products are a hazard to public health. They contribute to antimicrobial resistance (AMR) as the exposure of bacteria to trace amounts of these residues can hasten its incidence and emergence. In the Philippines, the quality of meat products is regulated by the National Meat Inspection Service (NMIS) through antimicrobial sensitivity testing (AST) via disc diffusion. Analytical methods such as the use of high-performance liquid chromatography (HPLC) may also be used in monitoring antibiotic residues in meat samples. This experimental study aims to develop a screening method for tetracycline residues in pork (Sus scrofa domesticus) muscle and liver from public wet markets; and to determine the feasibility of this method based on specified critical parameters such as LOD, LOQ, and linearity. Twenty (20) pork muscle and 14 pork liver samples were collected from stalls in three public wet markets and were subjected to AST through the NMIS and HPLC analysis. The HPLC analysis utilized an isocratic elution with a mobile phase of 85:15 0.1% formic acid in acetonitrile: 0.1% formic acid in water and a flow rate of 1.0 mL/min. The detection of tetracycline was observed at peaks with a retention time of 3.95 ± 0.15 min. The determined retention time was used to identify tetracycline in the pork samples. AST results showed no presence of tetracycline in all samples. HPLC results, however, revealed that two out of 20 pork muscle samples and eight out of 14 pork liver samples contained tetracycline. The results have demonstrated that instrumental methods of analysis such as HPLC are necessary to confirm the absence or presence of the residues and to quantify the concentration to compare it to the established MRL. Further validation studies are recommended to ensure the accuracy and specificity of the optimized method.